2009
DOI: 10.1016/j.mce.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary activators of Sirt1

Abstract: Calorie restriction (CR) is a non-genetic manipulation that reliably results in extended lifespan of several species ranging from yeast to dogs. The lifespan extension effect of CR has been strongly associated with an increased level and activation of the Sir2 histone deacetylase and its mammalian ortholog Sirt1. This association led to the search for potential Sirt1-activating, life-extending molecules. This review briefly outlines the experimental findings on resveratrol and other dietary activators of Sirt1. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 91 publications
1
59
0
1
Order By: Relevance
“…Resveratrol has been shown to increase lifespan and promote health span in model organisms ranging from yeast, worms, flies, and mice (Allard et al 2009;Pirola and Frojdo 2008). However, the prolongevity effect of resveratrol and its underlying mechanisms have been challenged by studies from several labs and remain controversial (Bass et al 2007b;Kaeberlein et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has been shown to increase lifespan and promote health span in model organisms ranging from yeast, worms, flies, and mice (Allard et al 2009;Pirola and Frojdo 2008). However, the prolongevity effect of resveratrol and its underlying mechanisms have been challenged by studies from several labs and remain controversial (Bass et al 2007b;Kaeberlein et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that SIRT1, an NAD + -dependent deacetylase, is a molecular target of resveratrol (27,34,35). We therefore tested whether administration of SRT1720, a small molecule activator of resveratrol, mimics the life-extending effect of resveratrol in nonresuscitated rats.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…An increased expression of SIRT1 is capable of extending the life span of model organisms and it appears that the activity of Sir2 (a homolog of SIRT1) is required for the lifeextending benefits of caloric restriction in organisms such as yeast and flies (10). SIRT1 levels are regulated by microRNAs (miRNAs) that have emerged as significant metabolic regulators (1).…”
Section: Resultsmentioning
confidence: 99%